Characterization of Cat’s Eye Dammar for Revision of Indonesia National Standard - Rita K Sari; Nyoman J Wistara; Arif Wijayanto; Totok K Waluyo (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
The present works was aimed to examine the concordance between trader quality classification and related SNI classification on dammar resin. The quality of six quality classes of dammar resin by trader classification was evaluated based on SNI 2900-1-2012 on visual classification and SNI 01-2900-1999 on physical and chemical characteristics, and then the resulting data were analyzed with ANOVA. The quality concordance of dammar resin based on trader classification with these of SNI for visual appearance and the size of agglomeration was 50 and 75-94%, respectively, and these of insolubility in toluene, melting point, ash content, and acid number were 61, 72, 11, and 100%, respectively. The characteristics of dammar resin for the a, b, and c quality classification were the same for the Krui traders, BKG Ltd., and WGM Ltd. However, they were different for the lower quality classification of d, e, and powder. It was also found the existence of dammar resin with characteristic values beyond the range of these established by SNI. SNI should not classify dammar resin quality based on visual appearance, but merely based on its physical and chemical characteristics. Physical and chemical characteristics values required by SNI should be revised.Key words: cat’s eye dammar, Indonesia National Standard, physical and chemical characteristics, quality classification, Shorea javanica